Ancestral sequence reconstruction of the CYP711 family reveals functional divergence in strigolactone biosynthetic enzymes associated with gene duplication events in monocot grasses. Issue 5 (25th June 2022) - Vinde, Marcos H.; Cao, Da; Chesterfield, Rebecca J.; Yoneyama, Kaori; Gumulya, Yosephine; Thomson, Raine E. S.; Matila, Tebogo; Ebert, Birgitta E.; Beveridge, Christine A.; Vickers, Claudia E.; Gillam, Elizabeth M. J.
Summary: The strigolactone (SL) class of phytohormones shows broad chemical diversity, the functional importance of which remains to be fully elucidated, along with the enzymes responsible for the diversification of the SL structure. Here we explore the functional evolution of the highly conserved CYP711A P450 family, members of which catalyze several key monooxygenation reactions in the strigolactone pathway. Ancestral sequence reconstruction was utilized to infer ancestral CYP711A sequences based on a comprehensive set of extant CYP711 sequences. Eleven ancestral enzymes, corresponding to key points in the CYP711A phylogenetic tree, were resurrected and their activity was characterized towards the native substrate carlactone and the pure enantiomers of the synthetic strigolactone analogue, GR24. The ancestral and extant CYP711As tested accepted GR24 as a substrate and catalyzed several diversifying oxidation reactions on the structure. Evidence was obtained for functional divergence in the CYP711A family. The monocot group 3 ancestor, arising from gene duplication events within monocot grasses, showed both increased catalytic activity towards GR24 and high stereoselectivity towards the GR24 isomer resembling strigol‐type SLs. These results are consistent with a role for CYP711As in strigolactone diversification in early land plants, which may have extended to the diversification of strigol‐type SLs.